Competition matters: Determining the drivers of land snail community assembly among limestone karst areas in northern Vietnam. Issue 8 (26th March 2018) - von Oheimb, Parm Viktor; von Oheimb, Katharina C. M.; Hirano, Takahiro; Do, Tu Van; Luong, Hao Van; Ablett, Jonathan; Pham, Sang Van; Naggs, Fred
Abstract: The insular limestone karsts of northern Vietnam harbor a very rich biodiversity. Many taxa are strongly associated with these environments, and individual species communities can differ considerably among karst areas. The exact processes that have shaped the biotic composition of these habitats, however, remain largely unknown. In this study, the role of two major processes for the assembly of snail communities on limestone karsts was investigated, interspecific competition and filtering of taxa due to geographical factors. Communities of operculate land snails of the genus Cyclophorus were studied using the dry and fluid‐preserved specimen collections of the Natural History Museum, London. Phylogenetic distances (based on a Bayesian analysis using DNA sequence data) and shell characters (based on 200 semilandmarks) were used as proxies for ecological similarity and were analyzed to reveal patterns of overdispersion (indicating competition) or clustering (indicating filtering) in observed communities compared to random communities. Among the seven studied karst areas, a total of 15 Cyclophorus lineages were found. Unique communities were present in each area. The analyses revealed phylogenetic overdispersion in six and morphological overdispersion in four of seven karst areas. The pattern of frequent phylogenetic overdispersion indicated that competition among lineages is the major process shaping the Cyclophorus communities studied. The Coastal Area, which was phylogenetically overdispersed, showed a clear morphological clustering, which could have been caused by similar ecological adaptations among taxa in this environment. Only the community in the Cuc Phuong Area showed a pattern of phylogenetic clustering, which was partly caused by an absence of a certain, phylogenetically very distinct group in this region. Filtering due to geographical factors could have been involved here. This study shows how museum collections can be used to examine community assembly and contributes to the understanding of the processes that have shaped karst communities in Vietnam. Abstract : In this study, the processes underlying community assembly of land snails ( Cyclophorus spp.) on northern Vietnam's island‐like limestone karsts were investigated based on museum collection material. Characters from molecular phylogenetics and shell morphology were used as proxies for ecological similarity and analyzed for patterns of overdispersion (indicating competition) or clustering (indicating filtering) in communities. Unique communities were present in each of the studied karst areas, and most of them have probably been shaped by competition rather than by filtering due to geographical factors.